Procedures and timetable for proposals to amend Chapter F of the International Code of Nomenclature for algae, fungi, and plants - Tom W. May (IMA Fungus)
Abstract Procedures for preparing and submitting proposals to amend or enhance Chapter F of the International Code of Nomenclature for algae, fungi, and plants are provided. Such proposals will be considered by the Fungal Nomenclature Session of the XII International Mycological Congress to he held in Amsterdam in 2022. A timetable is laid out for the submission of proposals, due by 31 December 2021, their publication in IMA Fungus, the appearance of the ‘Synopsis of proposals” and the conduct of the pre-Congress guiding vote.